Examining the influence of corporate governance on intellectual capital efficiency evidence from top service firms in Australia - Appuhami, R.; Bhuyan, Mohammed (Emerald Group Publishing Ltd., 2015)
The purpose of this paper is to examine the influence of corporate governance on intellectual capital (IC) in top service firms in Australia. Design/methodology/approach – Drawing on the agency theory, the paper develops hypotheses about relationships between corporate governance mechanisms (chief executive officer [CEO] duality, board size, board composition and subcommittee composition) and IC. The study uses a multiple regression analysis on data collected from corporate annual reports of 300 firm-year observations. Findings – The findings of the regression analysis indicate that CEO duality, board composition and remuneration committee composition are significantly associated with IC. In contrast, there is no evidence that board size and audit committee composition have an effect on IC. The study contributes to agency theory in general and the literature on IC and corporate governance more specifically. Practical implications – The findings of the study might be of interest to regulators, investment analysts, shareholders, company directors and managers in Australia, as well as academics, in designing corporate governance mechanisms to develop IC. Originality/value – Corporate governance is country-specific and, hence, its impact on managerial decisions leading to IC is different from country to country. This study provides empirical evidence on the relationship between corporate governance and IC in top service firms in Australia.